A Child's Determination: Supporting Parent to Cope with Depression in Elizabeth G. Bedia’s Balloons for Papa - Kusumayanti, Dina D.; Rofiuddin, Muhammad Arsy; Setiarini, R. (POETIKA, 2024)
In appealing to readers below the age of thirteen, picture books can prove formative in children’s mental growth and well-being. Nevertheless, despite their potential importance, few studies have explored children’s picture books that focus on children grappling with familial struggles and mental health, such as depression. This research therefore examined the children’s picture book, Balloons for Papa: A Story of Hope and Empathy, written by Elizabeth Gilbert Bedia and illustrated by Erika Meza, primarily aiming to reveal 1) how a child’s determination and depression are portrayed, and 2) the author’s ideology and critical position. A qualitative approach was taken to analyze the data. Hall’s representation theory, which focuses on the constructionist approach, was chosen to gain a better understanding of how the author's culture, situation, and society contributed to their creation of the book. Meanwhile, Barthes' semiotic approach was utilized as a tool to examine the illustrations. The findings underscored the empathetic qualities of Arthur, the main character of the story, which drive his relentless pursuit to restore his father's happiness. However, it is critically acknowledged that the representation of Papa may not offer a definitive portrayal of depression. Nevertheless, Bedia's narrative still aligns with the broader discourse on depression awareness and the resilience of a child's determination, contributing to a nuanced understanding of these complex themes within the context of the picture book. In addition to providing insight into the pivotal themes of hope, empathy, and mental well-being within the context of children's literature, this research unraveled the intricate interplay between hope and empathy, while also portraying a child's determination against the backdrop of depression.